Simulation photoconverters of porous-Si/Si with different anti-reflective coatings - Dyadenchuk, Alona; Oleksenko, Roman; Дяденчук, Альона Федорівна; Олексенко, Роман Іванович (My University, 2023)
ENG: This work is aimed at researching promising photosensitive solar energy structures based on the porous-Si/Si heterostructure with and without anti-reflective coatings. The PC1D program was used to model the photoconverted parameters. The reflection spectra of silicon solar cells without coating and with anti-reflective coatings SiO2, TiO2, ZnO, ZnS were studied. It was found that the reflection coefficient of the pure porous-Si/Si heterostructure at a wavelength about 500 nm reaches 37%, while the reflection coefficient from ARC is not more than 13% for the same wavelength in the case of light incidence at a 30º angle, and for the 45º angle incidence sunlight the value of the reflection coefficient becomes ⁓31% for porous-Si/Si and does not exceed 16% for solar cells with anti-reflective coatings at a wavelength about 500 nm. The light photoconverter characteristics were calculated on the basis of the studied structures, and the current-voltage characteristics were also constructed. Initial simulation results show that porous- Si/Si solar cells efficiency is about 17.5%. A significant increase in solar cells efficiency was achieved thanks to the use of anti-reflective coatings. Among the four materials, anti-reflective coatings TiO2 has the highest efficiency value, which reached 26.4%. Frontal surface texturing effect on solar cell efficiency was studied. In texturing absence, the efficiency of the porous-Si/Si solar cell was 17.1%, and with texturing it reached the 18.1% value. For structures with anti-reflective coating, the efficiency is 17.3% (SiO2), 25.4% (TiO2), 19.8% (ZnO), 19.8% (ZnS) without surface texturing and 18.3% (SiO2), 26.4% (TiO2), 20.7% (ZnO), 20.9% (ZnS) with texturing. Operating temperature effect on the electrical solar cell characteristics is considered. It was established that an increase in temperature leads to a decrease in the efficiency of the studied structures by: 2.5% (without anti-reflective coatings), 2.3% (SiO2), 1.8% (TiO2), 2.4% (ZnO), 2.9% (ZnS).///////////// UKR: Метою даної роботи є дослідження перспективних фоточутливих структур сонячної енергетики на основі гетероструктури пористий Si / Si з просвітлюючими покриттями і без них. Для моделювання фотоконвертованих параметрів використовувалася програма PC1D. ZnO, ZnS. Встановлено, що коефіцієнт відбиття чистої гетероструктури пористий Si/Si на довжині хвилі близько 500 нм досягає 37%, тоді як коефіцієнт відбиття від АРО становить не більше 13% для тієї ж довжини хвилі у разі падіння світла на 30°, а при вугіллі падіння сонячного світла 45° значення коефіцієнта відображення становить ⁓31% для пористого Si/Si і не перевищує 16% для сонячних елементів з просвітлюючими покриттями на довжині хвилі близько 500 нм. На основі досліджених структур були розраховані характеристики фотоперетворювача світла, а також побудовані вольт-амперні характеристики. 17,5%. Значного підвищення ефективності сонячних батарей вдалося досягти завдяки використання антивідблиску покриття Серед чотирьох матеріалів просвітлююче покриття TiO 2 має найбільше значення ефективності, яке досягло 26,4% Вивчено вплив текстурування фронтальної поверхні на ефективність сонячного елемента. з текстуруванням досягла значення 18,1%. Для конструкцій з просвітлюючим покриттям ефективність становить 17,3% (SiO2 ) , 25,4% (TiO2 ) , 19,8% (ZnO), 19,8% (ZnS) без текстурування поверхні та 18,3% (SiO2 ) , 26,4% (TiO2 ) ), 20,7% (ZnO), 20,9% (ZnS) з текстуруванням. Вплив робочої температури на електричні характеристики сонячного елемента. 2,4% ( ZnO ) , 2,9% (ZnS).
Keywords: solar cell; porous Si; PC1D; simulation; anti-reflective coating